Rodrick rules ebook - Kinney, Jeff (Diary of a Wimpy Kid, 2012)
In Rodrick Rules, book 2 of the Diary of a Wimpy Kid series from #1 international bestselling author Jeff Kinney, Greg Heffley's got a secret, and if anyone finds out the juicy details, his life is going to get turned inside out. Unfortunately, he's also got an older brother, Rodrick, who has a talent for sniffing these things out. But secrets can't stay under wraps for long—especially when there's a diary involved. Rodrick's band, Löded Diper, has never been so awful, and the laughs have never been so loud. Collect all the books in the #1 bestselling Diary of a Wimpy Kid series: Diary of a Wimpy Kid (#1) | Rodrick Rules (#2) | The Last Straw (#3) | Dog Days (#4) | The Ugly Truth (#5) | Cabin Fever (#6) | The Third Wheel (#7) | Hard Luck (#8) | The Long Haul (#9) | Old School (#10) | Double Down (#11) | The Getaway (#12) | The Meltdown (#13) | Wrecking Ball (#14) | The Deep End (#15) | Big Shot (#16) | Diper Överlöde (#17) | No Brainer (#18) | Hot Mess (#19) See the Wimpy Kid World in a whole new way with the #1 bestselling Awesome Friendly books, told from the perspective of Greg Heffley's best friend Rowley Jefferson: Diary of an Awesome Friendly Kid: Rowley Jefferson's Journal | Rowley Jefferson's Awesome Friendly Adventure | Rowley Jefferson's Awesome Friendly Spooky Stories